Sistem Deteksi Kebocoran Gas LPG Berbasis Arduino di Universitas Dr. Soetomo Surabaya - Popy Vitria Eviolina; Yudi Kristyawan; Edi prihartono (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2025)
Liquid Petroleum Gas, commonly known as LPG, is widely used in household activities, especially for cooking. However, its flammable nature makes this gas very hazardous if a leak occurs, which can result in an explosion that damages buildings, endangers the safety of those living there, and causes financial losses. Recently, the improper or unsafe use of LPG gas has led to numerous accidents and fires. This raises serious concerns for the people who use it. LPG gas leaks are often difficult to detect due to various factors, such as the absence of the gas's distinctive odor or the absence of people around the leak location. This study aims to detect gas leaks to minimize or prevent fires and LPG gas explosions. The methods in the research that will be carried out include identification, literature study, data collection, design, implementation, system testing, and conclusions. In this study, the design and implementation of an LPG gas leak detection system based on Arduino will be carried out to minimize this risk. The system will use MQ-2 to determine the concentration of LPG gas in the air. When a leak is detected, the Arduino microcontroller will process the input and automatically close the solenoid and activate the buzzer as an alarm. The implementation and testing results concluded that the system can detect LPG leaks above 600 ppm and respond effectively by cutting off the gas supply and providing an audible warning. This system is expected to improve household safety by providing early warning of gas leaks. Future developments may include integration with an Android app for smartphones, enabling more practical remote monitoring.